Does COVID-19 Affect the Course of Trophoblastic Gestational Disease in Partial Hydatidiform Moles; Is It A Viral or A Pandemic? - İbanoğlu, Mujde Can and Yılmaz Ergani, Seval and Uzunoğlu, İrem Özge and Savran Üçok, Belgin and Akdaş Reis, Yıldız and Yakut Yücel, Kadriye and İskender, Cantekin and Engin Üstün, Yaprak (Acta Medica, 2022)
Objective: Hydatiform mole (HM) is a non-malignant form of gestational trophoblastic disease (GTD) characterized by failure of normal fetal development and overgrowth of trophoblasts. With this retrospective cohort study, we planned to determine the incidence of PHM, etiology and progression rates to Gestational trophoblastic neoplasia (GTN) during the COVID-19 epidemic. Materials and Method: This retrospective cohort study was conducted in Ankara Etlik Zübeyde Hanım Women’s Health Training and Research Hospital Early Pregnancy Assessment Unit between March 2016 and February 2022. Patients who underwent therapeutic curettage (T/C) with the diagnosis of missed abortion, intrauterine exitus (IUEX), molar pregnancy or incomplete abortion after single spontaneous pregnancy were included in the study. The study group consisted of 138 patients who were diagnosed with partial hydatiform mole as a result of pathological examination in this process. There were 135 patients in the control group. Results: The number of patients who applied during the pandemic period and were diagnosed with PHM was 62 (44.92%). The mean age of the patients in the study group was 31.97±8.26 years. The mean body mass index of these patients was 26.38±5.13 m2/kg. The mean paternal age in the study group was 34.95±8.32 years, and it was higher than the paternal age of the patients in the control group (p=0.028). While the incidence of PHM was 1.22/1000 births in our hospital in 2019, this figure was calculated as 3.79/1000 births in 2020. The incidence of progression to GTN at 4 years before the pandemic was 0.02/1000 births; In 2020-2021, this rate was calculated as 0.25/1000 births. Conclusion: During the pandemic period, along with the increase in the incidence of PHM compared to the pre-pandemic period, an increase in the incidence of progression to GTN disease was detected.